1990
DOI: 10.1007/bf03159905
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of phosphatidylserine on the binding of muscarinic cholinergic receptor ligands

Abstract: The modulation of the binding of muscarinic cholinergic receptor ligands by phosphatidylserine purified from bovine cerebral cortex (BC-PS) was examined in vitro and in vivo. The enrichment of bovine cerebral cortical synaptosomal membranes with BC-PS, using a fusion technique, produced a concentration-dependent decrease in the affinity (increase in Kd) of [3H]quinuclidinyl benzylate (3H-QNB) specific binding to muscarinic acetylcholine receptors (mAChR), without changes in their maximal number (Bmax). Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…PtdSer may be involved in the signal-transduction events by facilitating activation of protein kinase C (PKC) [5], and it has been suggested that PtdSer regulates various receptors [6,7]. It has been reported that PtdSer may modulate the agonist binding to muscarinic cholinergic ligands [8]. Cellular activation by neurotransmitters, growth factors and hormones was accompanied by alterations of PtdSer synthesis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…PtdSer may be involved in the signal-transduction events by facilitating activation of protein kinase C (PKC) [5], and it has been suggested that PtdSer regulates various receptors [6,7]. It has been reported that PtdSer may modulate the agonist binding to muscarinic cholinergic ligands [8]. Cellular activation by neurotransmitters, growth factors and hormones was accompanied by alterations of PtdSer synthesis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%